2003
DOI: 10.1103/physrevb.67.125320
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of surface roughening of Cl-terminated Si(100)-(2×1) at 700 K

Abstract: The dynamics of surface roughening and healing induced by Cl on Si͑100͒-͑2ϫ1͒ were studied with variable-temperature scanning tunneling microscopy. Clean samples were exposed to Cl 2 at room temperature, heated to as high as 700 K, and imaged for periods that exceeded 20 h. Chlorine caused surface roughening via a Cl recycling pathway that created pits and regrowth islands with minimal desorption of SiCl 2. This reaction pathway is accessible at ϳ675 K if the surface is not saturated with Cl. Images showed dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 31 publications
(39 reference statements)
2
30
1
Order By: Relevance
“…These insights have important implications for Si(100) processing chemistry where defects of this kind are common. In particular, these results are not consistent with a recent claim regarding the distribution of Cl atoms on etched Si(100) surfaces [23].…”
contrasting
confidence: 68%
“…These insights have important implications for Si(100) processing chemistry where defects of this kind are common. In particular, these results are not consistent with a recent claim regarding the distribution of Cl atoms on etched Si(100) surfaces [23].…”
contrasting
confidence: 68%
“…This surface is far from equilibrium in that subsequent scans showed changes in average sizes for pits and RIs, as well as their surface areas. 10 Figure 5 shows the combined pit and RI areas as a function of time at 700 K for Cl-terminated Si͑100͒ surfaces. For i (Cl)ϭ0.3 and 0.5 ML, the combined area first increased quickly but it saturated after ϳ4 and ϳ8 h, respectively, as the surfaces reached dynamic equilibrium.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that dimer vacancy lines of odd lengths, 2Nϩ1 dimer vacancies, greatly outnumber those of even lengths, 2N, because odd lengths offer a rebonded symmetric redimerization configuration for the second-layer Si atoms and are energetically favorable. 25 This Comparison shows that the two BD's that were gray in ͑a͒ were dark in ͑b͒. ͑d͒ Schematic of the initial and final Br configurations in box II showing that electron injection perturbed the system and caused Br atoms to hop.…”
Section: B Atom Vacancy Line Internal Structure: "3ã2… Vs "3ã1…mentioning
confidence: 96%
“…24 In turn, elongation is assisted by the high surface stress at the ends of the atom vacancy lines. The atom vacancy line formation mechanism is the same as that for Cl-Si͑100͒, 25 but the atom vacancy lines are more numerous here because the Br-Br steric repulsion is stronger. 26 Thus, stress both lowers the barrier for dimer vacancy creation and is important in atom vacancy line formation.…”
Section: Introductionmentioning
confidence: 91%